Lateral epitaxial heterojunctions in single nanowires fabricated by masked cation exchange - Sedat Dogan (Nature Portfolio, 2018)
Lateral structuring of the chemical composition of nanowires can enhance their functionality for photoconductive devices. Here, the authors fabricate CdSe/Cu2Se nanowire heterojunctions with atomically sharp interfaces and epitaxial relationships by a masked cation exchange approach.